Magnetically controlled growing rods for rigid scoliosis: an alternative to halo-gravity traction in preparing for definitive correction? - Aldeeri, Riyadh; Al Mansour, Haidara; Kentar, Yasser; Hemmer, Stefan; Pepke, Wojciech; Akbar, Michael (Der Orthopäde, 2018)
The treatment concept for severe rigid idiopathic scoliosis is a short-term application of halo-gravity traction to enable maximum correction and subsequent dorsal fusion. The method has already been mentioned in the literature as an effective procedure. This case report demonstrates the use of a new treatment concept using magnetically controlled distraction rods as a possible alternative to the halo-gravity traction device. To our knowledge the use of this technique in severe rigid idiopathic scoliosis has not yet been published.
Gesehen am 04.05.2020